Accuracy and consequences of same-day, invasive lung cancer workup – a retrospective study in patients treated with surgical resection. Issue 1 (1st January 2016) - Madsen, Kirsten Riis; Høegholm, Asbjørn; Bodtger, Uffe
Abstract : Background: Though widely used, little is known about accuracy and efficacy of same-day, invasive workup of suspected lung cancer. Objective: To evaluate the accuracy and efficacy of same-day, invasive lung cancer workup (diagnosis and mediastinal staging), and to identify differences between patients without (Group A) or with (Group B) need for resampling. Methods: A retrospective study was performed on all consecutive patients referred for surgical treatment for localised lung cancer after invasive diagnostic and staging workup at our unit. Data were extracted from electronic medical files. Surgical specimens served as gold standard for correct diagnosis and stage. Results: A total of 129 patients (peripheral lesion: 84%; mediastinal staging: 97%) were included. After same-day, invasive workup, 71% had no need for further invasive workup (Group A), while 29% had (Group B). Group A differed significantly from Group B in fewer invasive tests, fewer days from referral to surgery, and lower pneumothorax incidence, while no differences were observed in diagnostic accuracy, cancer subtype, tumour size, tumour stage, peripheral lesion, nodal involvement, gender, or presence of chronic obstructive pulmonary disease. Tumour located in right upper lobe was associated with need for resampling. Discussion: Our retrospective study suggests that same-day, invasive workup for lung cancer is safe, accurate, and efficacious in reducing time to therapy, even in patients with small lesions and low tumour burden.